2002
DOI: 10.1053/jvet.2002.29455
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Free Tissue Transfer of the Rectus Abdominis Muscle in Dogs

Abstract: Objective— To assess donor‐site morbidity and survival of the rectus abdominis muscle with an overlying skin graft after free tissue transfer to a medial femorotibial defect in dogs. Study Design— Experimental study. Sample Population— Phase 1:6 canine cadavers; phase 2:7 adult mixed‐breed dogs. Methods— Phase 1: The rectus abdominis muscle was removed from canine cadavers, muscular and vascular dimensions were recorded, and angiography was performed. Phase 2: Muscular transfer was performed through anastomosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
11

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 52 publications
0
10
0
11
Order By: Relevance
“…In this case, blood flow in the microvascular anastomoses could not be reestablished, and the attempt failed 11 . Calfee et al 12 also have reported use of the rectus abdominis muscle as a free tissue transfer to the hindlimb. They suggested that free tissue transfer of the canine rectus abdominis muscle also may be beneficial for repair of facial wounds but did not examine this application specifically 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, blood flow in the microvascular anastomoses could not be reestablished, and the attempt failed 11 . Calfee et al 12 also have reported use of the rectus abdominis muscle as a free tissue transfer to the hindlimb. They suggested that free tissue transfer of the canine rectus abdominis muscle also may be beneficial for repair of facial wounds but did not examine this application specifically 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Calfee et al 12 also have reported use of the rectus abdominis muscle as a free tissue transfer to the hindlimb. They suggested that free tissue transfer of the canine rectus abdominis muscle also may be beneficial for repair of facial wounds but did not examine this application specifically 12 . In cases like those we report, in which the vascularity of the recipient site has been compromised, pedicle flaps are more likely to survive than free tissue transfers 1…”
Section: Discussionmentioning
confidence: 99%
“…The blood vessels were anastomosed with the recipient blood vessels on the medial aspect of the tibia. The muscle flap remained viable after the transfer and angiographic studies revealed that the muscle flap was consistently perfused by these blood vessels (21). Another study reported the successful use of the free microvascular flap transfer of the rectus abdominis muscle with the caudal epigastric blood vessels to promote healing of complicated extremity and oral wounds in nine dogs (18).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to human, the canine rectus abdominis muscle receives blood supply from two main sources: the cranial epigastric artery and vein penetrate the craniomedial aspect of the rectus muscle and supply the cranial third of the muscle. [8][9][10][11][12] The deep caudal epigastric artery and vein, similar to the deep inferior epigastric vessels in humans, enter the rectus muscle in the caudal lateral aspect and supply the caudal two-thirds of the muscle; however, the entire muscle can survive based on either pedicle, as in humans. [8][9][10][11][12] Unlike humans, however, the skin overlying the ventral abdomen in canine is not supplied by the perforators from the deep caudal epigastric artery.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] The deep caudal epigastric artery and vein, similar to the deep inferior epigastric vessels in humans, enter the rectus muscle in the caudal lateral aspect and supply the caudal two-thirds of the muscle; however, the entire muscle can survive based on either pedicle, as in humans. [8][9][10][11][12] Unlike humans, however, the skin overlying the ventral abdomen in canine is not supplied by the perforators from the deep caudal epigastric artery. Our findings are consistent with previous reports in that the caudal two-thirds of the abdominal skin, including the mammary glands 3 to 5, receives an axial pattern blood supply from the superficial caudal epigastric artery.…”
Section: Discussionmentioning
confidence: 99%